The love of my afterlife eaudiobook - Greenwood, Kirsty (Books on Tape, 2024)
A GOOD MORNING AMERICA BOOK CLUB PICK AN INSTANT USA TODAY BESTSELLER!  "This book has it all. Humor, heart, and a heroine I was desperately rooting for. Kirsty Greenwood has a new fan!” — Colleen Hoover , New York Times bestselling author A recently deceased woman meets “the one” in the afterlife waiting room, scoring a second chance at life (and love!) if she can find him on earth before ten days are up… If she wasn’t dead already, Delphie would be dying of embarrassment. Not only did she just die by choking on a microwaveable burger, but now she’s standing in her ‘shine like a star’ nightie in front of the hottest man she’s ever seen. And he’s smiling at her. As they start to chat, everything else becomes background noise. That is until someone comes running out of a door, yelling something about a huge mistake, and sends the dreamy stranger back down to earth. And here Delphie was thinking her luck might be different in the afterlife.   When Delphie is offered a deal in which she can return to earth and reconnect with the mysterious man, she jumps at the opportunity to find her possible soulmate and a fresh start. But in a city of millions, Delphie is going to have to listen to her heart, learn to ask for help, and perhaps even see the magic in the life she’s leaving behind…